2013
DOI: 10.1517/14728222.2013.789862
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ApoE4/ApoE receptor LRP1 in Alzheimer's disease

Abstract: Due to the recent setbacks in the clinical trials targeting AD, it is instrumental to seek alternative therapeutic approaches, which aim to reduce the accumulation of Aβ in the brain tissue. As the ApoE/LRP1-mediated clearance of Aβ across the BBB is the key event in the regulation of Aβ transcytosis from brain to periphery, direct targeting of this protein entity at the BBB holds a great potential in the treatment of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 127 publications
0
23
0
2
Order By: Relevance
“…A β 42 is the key neurotoxic and pro‐inflammatory component in AD,7, 8 but recent studies have also pointed toward a potential anti‐inflammatory role for A β 42 under certain conditions 13, 14. Since ApoE is the major mediator of A β clearance from the brain,44 we wanted to address potential changes in the plasma concentration of A β among different APOE groups. While plasma A β 40 and A β 42 levels remained unaffected between the different APOE groups , we observed a significant negative association between plasma A β 42 and hs‐CRP levels even after age adjustment, suggesting that A β 42 may confer protective effect(s) against peripheral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A β 42 is the key neurotoxic and pro‐inflammatory component in AD,7, 8 but recent studies have also pointed toward a potential anti‐inflammatory role for A β 42 under certain conditions 13, 14. Since ApoE is the major mediator of A β clearance from the brain,44 we wanted to address potential changes in the plasma concentration of A β among different APOE groups. While plasma A β 40 and A β 42 levels remained unaffected between the different APOE groups , we observed a significant negative association between plasma A β 42 and hs‐CRP levels even after age adjustment, suggesting that A β 42 may confer protective effect(s) against peripheral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, three major functions have been suggested for astrocyte-derived ApoE-containing lipoproteins: 1) the transfer of phospholipids and cholesterol via ATP-binding cassette (ABC) transporters such as ABCA1 and ABCG1 15 ; 2) interaction with the LDL receptor superfamily of proteins located on the surface of neurons to facilitate axonal growth and neuronal survival 16 ; and 3) interaction with the LDL receptor-related protein 1 (LRP1)-dependent cellular uptake pathway, in the deposition of amyloid plaques 17,18 . Although there is minimal direct interaction between ApoE and soluble Aβ in CSF 19 , apoE isoforms in ApoE-containing lipoprotein complexes can regulate the metabolism of soluble Aβ bycompeting for the binding of LRP1 with Aβ in astrocytes 19,20 .…”
Section: Lipoprotein Synthesis Assembly and Metabolism In Astrocytesmentioning
confidence: 99%
“…Liu et al showed increased level of APOE in LDL-receptor knockout mice, which resulted in decrease of the cholesterol levels in the brain (Liu et al 2010b). Due to the involvement of the LDL receptors in the clearance of Aβ associated with BBB permeability, it was suggested that these modulating agents could be potentially considered for treatment of AD (Martiskainen et al 2013). …”
Section: Introductionmentioning
confidence: 99%